Inspeksi Keselamatan Jalan di Ruas Jalan Tol Palimanan – Kanci - Widyaningrum, Shiska Wahyu; Basuki, Ahmad (VISA: Journal of Vision and Ideas, 2025)
Road safety is an important aspect of transportation infrastructure management to reduce the risk of traffic accidents. This study aims to evaluate road safety on the Palimanan – Kanci Toll Road section using the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method. The research approach is contingent, with the collection of primary and secondary data. The results of the safety inspection show that there are several locations with a high risk of accidents, especially in areas with suboptimal guardrails, roadsides that are prone to losing balance, as well as illegal parking activities and hawkers that interfere with the smooth flow of traffic. From the HIRIARC analysis, it was found that most danger points have a high risk level to extreme risk, which has the potential to increase the number of fatal accidents. This study proposes several mitigation strategies using engineering, education, and law enforcement methods. The implementation of these measures is expected to improve the safety of road users and reduce the number of accidents on the Palimanan – Kanci Toll Road.